2016
DOI: 10.1089/lgbt.2015.0051
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal HIV Testing Uptake Among Men Who Engage in Commercial Sex Work with Men in Asia

Abstract: While one might expect a high HIV testing rate among MSMSW due to the risks associated with engaging in sex work, we found that HIV testing uptake is suboptimal among MSMSW in Asia. These results suggest that targeted HIV prevention and testing promotion among MSMSW are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…Also, our multivariable analysis showed that alcohol consumption and drug use were not significantly associated with HIV testing, contrary to the finding of an RDS study among 243 YMSM aged 15 to 24 years in Chiang Mai, Thailand . However, we found that increasing number of male sex partners was associated with higher odds of having tested for HIV, a finding similar to that of other studies conducted among MSM in Cameroon, China and other Asian countries . It is likely that HIV testing behaviour reflects perceived risk of HIV infection among MSM; ones who have multiple male sexual partners may perceive themselves at high risk, while others who have never tested may not perceive themselves or their partners as “risky” .…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Also, our multivariable analysis showed that alcohol consumption and drug use were not significantly associated with HIV testing, contrary to the finding of an RDS study among 243 YMSM aged 15 to 24 years in Chiang Mai, Thailand . However, we found that increasing number of male sex partners was associated with higher odds of having tested for HIV, a finding similar to that of other studies conducted among MSM in Cameroon, China and other Asian countries . It is likely that HIV testing behaviour reflects perceived risk of HIV infection among MSM; ones who have multiple male sexual partners may perceive themselves at high risk, while others who have never tested may not perceive themselves or their partners as “risky” .…”
Section: Discussioncontrasting
confidence: 74%
“…We estimated only half of the YMSM population in our study had recently tested for HIV, a lower figure compared to the proportion of MSM population aged 18 to 49 years who have tested for HIV and received their results in the past 12 months, reported from an RDS survey in four townships of Yangon, Mandalay, Pathein and Monywa in 2010 (62%, 95% CI: 55% to 70%) [57]. With evidence from research conducted in LMICs consistently indicating that YMSM are much less likely to access HIV testing as compared to older MSM [58][59][60][61], greater efforts are urgently needed to increase HIV testing coverage among this targeted population.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 50% of HMSW reported not testing for HIV in the past 12 months. Non-testing for HIV was common in prior studies from Asia and Africa [34][35][36]. A study of HMSW in Singapore found that only 27% had tested for HIV or STIs in the past 6 months [34].…”
Section: Discussionmentioning
confidence: 99%
“…A study of HMSW in Singapore found that only 27% had tested for HIV or STIs in the past 6 months [34]. In China, only 48.6% of MSW who have sex with men had tested for HIV [35,36]. In Kenya, a study found low prevalence (26%) of recent HIV testing among MSW [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation